The Influence of Infant Schema Cues on Donation Intention in Charity Promotion - Yang, Chen; Zhao, Mengying; Xie, Chunya; Li, Jingyi (Frontiers in Psychology, 2022)
This research performed four experiments to investigate the influence of infant schema cues on charitable donation intention and examine the moderating effect of gender. The results indicate that: (1) individuals stimulated by infant schema (vs. adult schema) cues had a higher willingness to donate when facing charity promotion; (2) the main effect was not due to the perceived cuteness of character in posters; (3) empathy played an entirely mediating role in the relationship between infant schema cues and donation intention; (4) gender moderated the influence of infant schema on donation intention: infant schema cues are effective for improving females’ donation intention, but ineffective for males. These findings contributed to the literature on infant schema and provide practical significance for introducing infant schema in charity promotion.